Predicting the Performance of CSA Technologies under current and future conditions - Lamanna, Christine; Steward, Peter R.; Kindt, Roeland; Rosenstock, Todd S. (2019)
Predicting the Performance of CSA Technologies under current and future conditions. Presentation at the Global Science Conference for Climate-Smart Agriculture 8-11 October 2019. Bali, Indonesia.